PENGARUH FINANCIAL TARGET, FINANCIAL STABILITY TERHADAP FRAUD LAPORAN KEUANGAN DENGAN KUALITAS LABA SEBAGAI VARIABEL MODERASI - Ririn Sari Dewi; Iroh Rahmawati; Rismawati (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of financial target and financial stability on financial statement fraud, with earnings quality as a moderating variable. Using panel data from 48 companies over the 2020–2022 period and applying the Common Effect Model (CEM), this research investigates whether managerial pressure in the form of financial goals and corporate stability contributes to the manipulation of financial statements. The statistical test results indicate that neither financial target nor financial stability has a significant effect on financial statement fraud. Likewise, earnings quality does not significantly moderate the relationship. The low R-squared value suggests that these internal financial factors are insufficient to explain the variations in fraudulent behavior. These findings highlight the importance of expanding fraud detection approaches by including external factors such as stakeholder pressure and regulatory enforcement. This study contributes to a deeper understanding of the financial determinants of reporting integrity in corporate settings.